In Vivo Healing Potential of Aegle marmelos in Excision, Incision, and Dead Space Wound Models - M. K. Gautam; V. Purohit; M. Agarwal; A. Singh; R. K. Goel (The Scientific World Journal)
The study incorporates the wound healing potential of Aegle marmelos fruit pulp extract (AME) on excision, incision, and dead space wound models in rats. AME (200 mg/kg) was administered orally once daily for variable days depending on the type of wound ulcer study. AME was studied for its wound breaking strength (incision wound), rate of contraction, period of epithelization and histology of skin (excision model), and granulation tissue free radicals, antioxidants, acute inflammatory marker, and connective tissue markers and deep connective tissue histology (dead space wound). Complete wound contraction and epithelization were observed at the 20th day after treatment with AME as compared to the 24th day in control rats. Mean epithelization period and scar area were decreased while wound breaking strength was increased with AME compared with control. Granulation tissue showed increased levels of collagen determinants (33.7 to 64.4%, P<0.001) and antioxidants (13.0 to 38.8%, P<0.05 to P<0.001), whereas markers of oxidative stress (55.0 to 55.6%, P<0.001) and myeloperoxidase (21.3%, P<0.001) were decreased in AME treated group. A. marmelos seems to promote wound healing by enhancing connective tissue formation and antioxidants status with decrease in free radicals and myeloperoxidase having tissue damaging effects.